High Optical Throughput and Low-Cost Spectral Sensing Using Photonic Structures - Khodadadzadeh, Iman (University of Waterloo, 2016)
Spectral sensing is an accurate means of probing the environment in a non-invasive manner. One of the most common instruments to acquire spectral data is a spectrometer. Spectrometers continue to improve in throughput and resolution while becoming smaller in size. However, the improvements in optics, gratings and detector performance have plateaued in free-space spectrometers due to fundamental trade-off between the spectral resolution and throughput of the spectrometer slit. Free space optical slicers on the other hand, have shown that this trade off can be broken using a complex optical setup. With the advent of nanophotonics and integrated optics, light can be routed and interact in a much smaller footprint. While integrated optics approach provides a more robust and smaller footprint, the throughput is still an issue since most designs only work with a very narrow band and single mode input. In this thesis, the concept of far-field beam forming is explored using mode coupling principles to increase the throughput of a spectrometer using photonic structures and waveguides. Three designs are provided that use the interaction between the modes to couple light between different size apertures at input and output. These designs use multi-mode input fibers and could operate on a wider wavelength range since they are not wavelength specific resonant based structures. They are fabricated and experimentally tested to measure their performance against a conventional free space slit. While spectrometers provide the full-range spectral information, application specific photonic sensors that use multi-spectral sensing approach are also promising fields of re- search. In this thesis, two such sensor designs are discussed. A multi-slot bio-sensor design is proposed as well as its optimization procedure to increase the refractive index sensitivity by 3×. Due to similarities between this design and the tapered waveguide designs for the spectrometer, the fabrication techniques developed for the photonic slit concept can be extended and applied for fabrication of this sensor. In addition, to avoid the system design and measurement complexities of a spectrometer or a ring resonator based sensor, a simple periodic array of silicon nanowire is proposed as a refractive index sensor. By considering the movement of diffraction spots at multiple wavelengths, refractive index resolution of 10 −5 or higher can be achieved.
Keywords: Spectroscopy; Integrated Photonics; Nanofabrication; Silicon Nanowires; optical sensing; Electron Beam Lithography; Integrated Spectrometer; Photonic Slicer